2022
DOI: 10.1111/jcmm.17404
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory properties of lemon‐derived extracellular vesicles are achieved through the inhibition of ERK/NF‐κB signalling pathways

Abstract: Chronic inflammation is associated with the occurrence of several diseases. However, the side effects of anti‐inflammatory drugs prompt the identification of new therapeutic strategies. Plant‐derived extracellular vesicles (PDEVs) are gaining increasing interest in the scientific community for their biological properties. We isolated PDEVs from the juice of Citrus limon L. (LEVs) and characterized their flavonoid, limonoid and lipid contents through reversed‐phase high‐performance liquid chromatography coupled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 61 publications
2
29
0
Order By: Relevance
“…Interestingly, PDNVs from different plant species, e.g., ginger rhizome [ 12 , 15 , 17 ], grapefruit [ 15 , 16 , 18 ], blueberries [ 13 ], broccoli [ 19 ], lemon [ 20 ] and cabbage [ 11 ] were shown to have anti-inflammatory activities in vitro and in vivo. The mechanisms underlying the anti-inflammatory effects of PDNVs include the induction of anti-inflammatory cytokines (IL-10, IL-22), suppression of pro-inflammatory cytokines (IL-6, IL-1β and TNF-α), induction of heme oxygenase-1 (HO-1), activation of nuclear factor (erythroid-derived 2)-like 2 (Nrf2) or the inhibition of ERK/NF-κB signaling pathways [ 15 , 20 ]. The molecules in pristine PDNVs with anti-inflammatory activities could be diverse including miRNAs, secondary metabolites, fatty acids, peptides and proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, PDNVs from different plant species, e.g., ginger rhizome [ 12 , 15 , 17 ], grapefruit [ 15 , 16 , 18 ], blueberries [ 13 ], broccoli [ 19 ], lemon [ 20 ] and cabbage [ 11 ] were shown to have anti-inflammatory activities in vitro and in vivo. The mechanisms underlying the anti-inflammatory effects of PDNVs include the induction of anti-inflammatory cytokines (IL-10, IL-22), suppression of pro-inflammatory cytokines (IL-6, IL-1β and TNF-α), induction of heme oxygenase-1 (HO-1), activation of nuclear factor (erythroid-derived 2)-like 2 (Nrf2) or the inhibition of ERK/NF-κB signaling pathways [ 15 , 20 ]. The molecules in pristine PDNVs with anti-inflammatory activities could be diverse including miRNAs, secondary metabolites, fatty acids, peptides and proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Lipid is an integral part of the bilayer membrane structure of PELNs, which affects the stability, uptake, and other biological functions of PELNs . Through the analysis of the lipid composition of CELNs, we found that DG accounted for 45%, which was much higher than the other three PELNs (lemon, grape, and ginger). ,,, Therefore, we speculate that DG may play a significant role in the fusion of cells and CELNs. As early as 1973, DG was found to promote membrane fusion .…”
Section: Discussionmentioning
confidence: 79%
“…HPLC/MS analysis was performed by adapting previously reported methods [ 21 , 22 ]. Samples for HPLC (Agilent 1260 Infinity) were prepared by collecting spent media from cultures (1 mL).…”
Section: Methodsmentioning
confidence: 99%